COMPARISON BETWEEN EFFICACY OF TYGECYCLINE AND MINOCYCLINE IN MULTI DRUG RESISTANT ACINETOBACTER BAUMANII ISOLATED FROM RESPIRATORY TRACT INFECTIONS - khan, Fouzia; Fatima, Ambreen; Gohar, Hareem; Sajjad, Mehwish; Iqbal, Sahar (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
Corona Virus (COVID)- 19 is a pathogenic viral infection that presents as a new worldwide public health crisis. This review article aims at recapitulating waves of COVID-19, vaccination programs, treatment options, and the current scenario of COVID-19 in Pakistan. All available literature on PubMed, Scopus databases and science direct and Google scholar relating to COVID-19 published between 2019 to January 2022 was reviewed. The first wave of COVID-19 presented as severe acute respiratory syndrome. The second wave had a modest intensity, affecting only Sindh's southern province, and peaked in mid-December 2020. The third wave, which primarily disturbed the regions of Khyber Pakhtunkhwa and Punjab, peaked in the late April 2021, when a new strain of SARS-CoV-2 was discovered in over 64 countries, including Pakistan, as of January 27, 2021. Fourth wave qualifying measures was forced in May, after which cases balanced out and most of the mortality was reported in Punjab, followed by Sindh. The 5th wave with a positive ratio in Karachi had the increasing trend from 2% to 6%. In clinical trials, treatment with a combination of Azithromycin and Chloroquine shown efficacy against COVID-19. The Tocilizumab was used to treat COVID-19–related symptoms. Vaccination appeared to be vital to control the COVID-19 disease outbreak with seven licensed vaccines. Currently 72% Pakistani population is either vaccinated or have been infected at least once.